Expression Pattern and Value of Brain-Derived Neurotrophic Factor in Periodontitis - He Chen; Xubo Feng; Qian Yang; Kaicheng Yang; Shasha Man (Elsevier, 2023)
Background: Periodontitis is a common human disease with an increasing incidence. Brain-derived neurotrophic factor (BDNF) is known to play a crucial role in the regeneration of periodontal tissue; however, the expression, methylation level, molecular function, and clinical value of BDNF in periodontitis require further investigation. This study aimed to investigate the expression and potential functions of BDNF in periodontitis. Methods: RNA expression and methylation data were obtained from the Gene Expression Omnibus (GEO) database, and the expression and methylation levels of BDNF were compared between periodontitis and normal tissues. In addition, bioinformatics analysis was performed to investigate the downstream molecular functions of BDNF. Finally, Reverse transcription Quantitative real-time polymerase chain reaction was performed to determine the level of BDNF expression in periodontitis and normal tissues. Results: GEO database analysis revealed that BDNF was hypermethylated in periodontitis tissues and that its expression was downregulated. Reverse transcription Quantitative real-time polymerase chain reaction confirmed that BDNF expression was downregulated in periodontitis tissues. Several genes that interact with BDNF were determined using a protein-protein interaction network. Functional analysis of BDNF revealed that it was enriched in the Gene Ontology terms cytoplasmic dynein complex, glutathione transferase activity, and glycoside metabolic process. Kyoto Encyclopedia of Genes and Genomes analysis suggested that BDNF was associated with the mechanistic target of rapamycin signaling pathway, fatty acid metabolism, the Janus kinase-signal transducer and activator of transcription signaling pathway, glutathione metabolism, and others. Furthermore, the level of BDNF expression was correlated with the immune infiltration degree of B cells and CD4+ T cells. Conclusions: This study shown that BDNF was hypermethylated and downregulated in periodontitis tissues, which could be a biomarker and treatment target of periodontitis.